2008
DOI: 10.1007/s00431-007-0642-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylprednisolone pulse on cytokine levels in Kawasaki disease patients unresponsive to intravenous immunoglobulin

Abstract: This study aimed to determine the effects of intravenous methylprednisolone pulse (IVMP) therapy on cytokine levels in patients with acute Kawasaki disease (KD) unresponsive to initial intravenous immunoglobulin (IVIG) therapy. Fifteen KD patients unresponsive to initial IVIG, 2 g/kg/day, were randomized to receive IVMP (n = 7), 30 mg/kg/day for 3 days or additional IVIG (n = 8), 2 g/kg/day, and plasma cytokine levels were compared. The fraction of febrile patients was significantly lower in the IVMP group tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 15 publications
(21 reference statements)
0
58
0
Order By: Relevance
“…Takahara et al [14] reported that levels of IL-6 in PE fluid decreased after PE, while sTNF-aR type 1 and type 2 remained at a high level. However, a randomized trial to compare IVMP with additional IVIG for refractory KD by Miura et al [9] revealed IVMP reduced TNF-a more profoundly than IVIG. Thus, the combination of IVMP and PE might decrease the levels of IL-6 and TNF-a.…”
Section: Discussionmentioning
confidence: 96%
“…Takahara et al [14] reported that levels of IL-6 in PE fluid decreased after PE, while sTNF-aR type 1 and type 2 remained at a high level. However, a randomized trial to compare IVMP with additional IVIG for refractory KD by Miura et al [9] revealed IVMP reduced TNF-a more profoundly than IVIG. Thus, the combination of IVMP and PE might decrease the levels of IL-6 and TNF-a.…”
Section: Discussionmentioning
confidence: 96%
“…Four trials examined high-dose methylprednisolone 'pulses' (IVMP) in combination with IVIG, either as primary combination therapy [50,51 ] or as adjunctive treatment after inadequate IVIG response [52,53]. The first was a randomized, double-blind, placebo-controlled trial [50] of a dose of 30 mg/kg methylprednisolone (101 individuals) or placebo (98 individuals), followed by IVIG 2 g/kg and standard aspirin therapy.…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…The most utilized treatment is the application of Intravenous gammaglobulin (GGIV) at a dose of 2 per kg in a sole dose for a 12-infusion; this is the most accepted treatment and has allowed to the reduction of prevalence of aneurysms to <5% and a mortality of 2% to 0.3%, although the GGIV scheme is at a dosage of 400 mg × kg × day for 5 days, plus aspirin at 80 to 100 mg × kg × day. According to response, the GGIV dose can be repeated, or corticoids can be added, especially in refractory cases (Cha, 2008;Chung, 2009;Falcini, 2006;Hung, 2009;Miura, 2008;Newbauer, 2004;Ogata, 2009;Okada, 2009;Sano, 2010;Tremoulet, 2008).…”
Section: Treatmentmentioning
confidence: 99%
“…Concerning recommendation for treatment of KD during the past 3 years, it as been mentioned that the greatest effectiveness in cases of relapse or resistance is obtained on utilizing pulses of methylprednisolone in addition to GG. In cases of recurrence of fever or resistance to GGIV, this combination has even been recommended as initial therapy (Cha, 2008;Chung, 2009;Miura, 2008;Ogata, 2009;Okada, 2009;Sha, 2008). Cardiovascular sequelae of KD in the adult in Japan.…”
Section: Treatmentmentioning
confidence: 99%